The Impact Of Traditional Games On Students' Cooperation Ability In Physical Education - Iis Rumaeso; Ayi Suherman; Anin Rukmana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Problems in education in Indonesia in the formation of student character and the urgency in preserving traditional games as national heritage are the background for this research. Characteristics of cooperation that must be instilled in students can be done through traditional games which contain moral values. This research is experimental research with a one group pretest posttest design to see the effect of applying traditional games in physical education learning on students' collaboration abilities. The games used include bakiak, galaasin, fortification, boy-boyan, dragon snake. The research subjects consisted of thirty fifth grade students at SDN Karamatmulya 02 in Bandung Regency. Data collection uses a questionnaire. The research results obtained t count (7.902) > t table (2.042) and a significant value (0.00 < 0.05) meaning that Ho was rejected and Hi was accepted. From the hypothesis test, it can be seen that there is a significant difference in students' collaboration abilities before and after being given traditional game treatment.